Obstetrics and perinatal outcomes in pregnancies complicated by diabetes and control pregnancies in an Indian tertiary care center - Suman, Akanksha; Kumar, Arvind (Orapuh Journal, 2024)
Introduction Obstetric diabetes, including pregestational and gestational diabetes, is associated with severe risks to both mother and child. Purpose This paper examined the effects of diabetes on obstetric and perinatal pregnancy outcomes and highlights the value of preventative care. Methods 200 pregnant women participated in the study, which took place in a tertiary care facility. Population characteristics, obstetric outcomes, and newborn outcomes were all quantified in this data set. Descriptive statistics and appropriate comparison tests were run in the statistical analysis. Results This retrospective study of 200 pregnant women shows that pregnancies complicated by diabetes have unique characteristics and outcomes compared to the control group. Pregestational diabetes was found in 55% of diabetic pregnancies, substantially correlated with older and heavier mothers (p <0.001). Seventy % of diabetic pregnancies required insulin therapy, and 22% of diabetic pregnant women experienced hypertension, compared to 12% of control pregnant women (p = 0.046). Higher birth weights, poorer 1-minute Apgar ratings, and higher risks of neonatal Hypoglycemia and NICU admissions were seen among infants born to women with diabetes. Preeclampsia was more common in pregnant women with diabetes (15%) than in the control group (8%; p = 0.109). Conclusion The findings of this study highlight the importance of preventative management and specialised treatment for women with diabetes who are expecting a child. Consistent with other research, these results prove that maternal diabetes is associated with both mother and child adverse outcomes. Improving maternal and foetal outcomes in diabetes-complicated pregnancies requires optimising glycemic control, preconception counselling, and multidisciplinary treatment.